Pengaruh Content Sharing, Viral Marketing dan Epistemic Value Terhadap Keputusan Pembelian Sunscreen Azarine pada Aplikasi Tiktok Berdasarkan Perspektif Etika Bisnis Islam: Studi pada Mahasiswa Dikota Bandar Lampung - A. Zuliansyah; Nurhayati Nurhayati; Ade Khairun Nisa (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This study aims to test the influence of content sharing, viral marketing, and epistemic value on the purchasing decision of Azarine sunscreen and its views in the Perspective of Islamic Business Ethics on Students in Bandar Lampung City. This study uses a quantitative approach. This study was conducted on students in Bandar Lampung. City who know about Azrarine sunscreen products and use the TikTok application with a population of 90,302 people. Sampling using purposive sampling, to determine the number of samples using the Solvin formula which got 100 people. The analysis method uses SPSS 25. The tests carried out are data validity and reliability tests, analysis prerequisite tests and hypothesis tests.The test results show that Content Sharing partially has no effect on the purchase decision of Azarine sunscreen. While simultaneously (together) the variables of content sharing, viral marketing, and epistemic value have a significant positive effect on the purchase decision of Azarine sunscreen on the TikTok application according to students in Bandar Lampung City,